The Differences of Marital Satisfaction of ODHA Couples with and without Depression Symptoms - Muhammad Ismail Salahudin; Alifiati Fitrikasari; Muchlis Achsan Udji Sofro; Hari Peni Julianti (Jurnal Penyakit Dalam Indonesia)
Introduction. HIV/AIDS disease has caused physical, social, and emotional problems to infected individuals and their spouses. ODHA couples have a prevalence of depression symptoms with physical complaints, which amounted to 12.7%. There is a relationship between love, communication, and physical intimacy to satisfaction in marriage. Depression in ODHA couples is correlated with marital satisfaction. This study aimed to analyze the differences of marital satisfaction of ODHA HIV negative couples who experience depression symptoms with ODHA who do not experience depression symptoms